2018
DOI: 10.26434/chemrxiv.7502210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Many-Body Effects Determine the Local Hydration Structure of Cs+ in Solution

Abstract: <div> <div> <div> <p>A systematic analysis of the hydration structure of Cs+ ions in solution is derived from simulations carried out using a series of molecular models built upon a hierarchy of approximate representations of many-body effects in ion-water interactions. It is found that a pairwise-additive model, commonly used in biomolecular simulations, provides poor agreement with experimental X-ray spectra, indicating an incorrect description of the underlying hydration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 0 publications
0
44
0
Order By: Relevance
“…Analyses of the interaction and many-body energies calculated for small Cs + (H 2 O) n cluster as well as the Cs + -oxygen RDF calculated from MD simulations of a single Cs + ion in water demonstrate that the new MB-nrg PEFs derived from the reduced-size training sets generated through AL display the same accuracy of the original MB-nrg PEF derived from the full 2B and 3B pools. 13,60 Given the computational cost associated with reference CCSD(T) calculations of individual many-body energies, our AL framework is particularly well-suited to the development of manybody PEFs, with chemical and spectroscopic accuracy, which can then be used in MD simulations of the target molecular system, from the gas to the condensed phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses of the interaction and many-body energies calculated for small Cs + (H 2 O) n cluster as well as the Cs + -oxygen RDF calculated from MD simulations of a single Cs + ion in water demonstrate that the new MB-nrg PEFs derived from the reduced-size training sets generated through AL display the same accuracy of the original MB-nrg PEF derived from the full 2B and 3B pools. 13,60 Given the computational cost associated with reference CCSD(T) calculations of individual many-body energies, our AL framework is particularly well-suited to the development of manybody PEFs, with chemical and spectroscopic accuracy, which can then be used in MD simulations of the target molecular system, from the gas to the condensed phase.…”
Section: Discussionmentioning
confidence: 99%
“…short . 60 The coefficients of both 2B and 3B PIPs were optimized using Tikhonov regression (also known as ridge regression) 62 to reproduce reference interaction energies obtained from high-level electronic structure calculations.…”
Section: A Mb-nrg Potential Energy Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] Despite their central role in mediating several physicochemical transformations in aqueous environments, the driving forces and mechanisms that determine the hydration structure of different ions remain the subject of ongoing debate. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] At the molecular level, a fundamental understanding of ion hydration is tightly connected to the ability to accurately characterize the structure and dynamics of the surrounding water hydrogen-bond (HB) network. Due to their relatively small size, small ion−water clusters represent prototypical systems for detailed studies of the rearrangements of the water HB network since they can be investigated both experimentally, using high-resolution vibrational spectroscopy, and theoretically, using high-level molecular modeling.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis of the hydration structure of Cs + in bulk water has shown that an accurate representation of individual low-order many-body interactions is necessary to quantitatively reproduce the experimental extended X-ray absorption fine structure (EXAFS) spectra. 25 Among small Cs + (H 2 O) n clusters, Cs + (H 2 O) 3 represents a particularly interesting case of isomer selectivity, displaying several low-energy isomers whose structures result from a subtle competition between water−water and ion−dipole interactions. This competition leads to a unique temperature dependence of the measured infrared spectrum of Cs + (H 2 O) 3 as multiple isomers are populated, even at cryogenic temperatures.…”
Section: Introductionmentioning
confidence: 99%